THE CONFLICT AROUND THE VSEVOLZHSKYS’ FISHING CRAFTS IN 1853-1856 - Tatyana Viktorovna Belikova (Гуманитарные и юридические исследования)
The article analyses the conflict around Vsevolozhskys’ fishing crafts in 1853-1856. It was a result of the introduction of repurchase of transporting salt from salt lakes to the shops of the Stavropol region.